Trace Elements in Abiotic and Biotic Environments - Kabata-Pendias, Alina (Taylor & Francis, 2015)
Trace Elements in Abiotic and Biotic Environments helps readers understand the fundamental principles and phenomena that control the transfer of trace elements. This book describes the occurrence and behavior of trace elements in rocks, soil, water, air, and plants, and also discusses the anthropogenic impact to the environment. In addition, it covers the presence of trace elements in feeds, as either contaminants or as nutritional or zootechnical additives, and their transfer across the food chain to humans. Also discussed is international legislation on trace elements for both micronutrients and contaminants in soil and plant food. A special focus is placed on the human health effects of both trace element deficiency and excess. All trace elements are covered-from aluminum to zirconium-as well as rare-earth elements (actinides and lanthanides).